EXPLORING SYNTACTIC CHALLENGES IN INDONESIAN-ENGLISH INTERPRETING: A STUDY ON EFL INTERPRETING STUDENTS - Fahria Malabar (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The study investigates the challenges faced by EFL interpreting students of Universitas Negeri Gorontalo (UNG) in translating Indonesian to English, focusing on the impact of syntactic structures, grammatical accuracy, and lexical choices on interpretation clarity. Using Gile’s (2020) syntactic analysis model, the research analyzes students’ translations to identify common errors, including tense shifts, inconsistent pronoun usage, and unidiomatic phrasing. The findings reveal that these issues often result from differences between Indonesian and English sentence structure, and limited understanding of English idiomatic expressions. For example, errors such as translating gender-neutral pronouns inaccurately or misinterpreting tense and modal constructions distort the source message’s meaning. The study underscores the need for targeted training in syntactic analysis, idiomatic adaptation, and cross-linguistic processing to improve EFL students’ ability to produce accurate and fluent interpretations. This research contributes to the understanding of linguistic and cognitive challenges in EFL interpreting.